The Initial Development and Validation of Physical, Psychosocial and Fatigue Level Questionnaire - Binti Ismail, Alya Nadhirah; Widia, Mirta; Binti Sukadarin, Ezrin Hani (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2024)
The lack of comprehensive tool to assess both risk factors of physical and psychosocial risk factors as well as fatigue level effectively is significant in similar field research. Therefore, the aim of this study is to do the initial development and content validation of a questionnaire that identifies and measures the risk factors influencing the fatigue levels. The questionnaire was developed by implementing adapt method followed by item generation in the initial development. This questionnaire was then validated in terms of content validation by expert panel reviews. The content validity result are as follows: 64-items out of 146-items scale had I-CVI below 1, 24-items with I-CVI of 0.8, and 3-items with 0.7, and the remaining items had I-CVI of below than 0.7. The average value of CVR was 1, and the S-CVI/Ave of the questionnaire was 0.93. Items with content validity of 0.7 and above was maintained, therefore, the questionnaire ended with 87-items. Findings indicates that the questionnaire is valid for assessing the physical and psychosocial risk factors associating with the fatigue levels. This questionnaire can be made a tool in assessing workplace while promote efficiency through this comprehensive tool, contributing to a better understanding of occupational risks and potential interventions.